Financing the Expansion of Cities, 1860-1914 - Platt, D. (Urban History Review / Revue d'histoire urbaine, 1983)
The expansion of Western cities in the period 1860-1914 required massive amounts of capital. At best, however, municipalities made only a modest contribution to the total expenditure before 1914. This was the case despite the varying beliefs about the role of cities, ranging from the "gas-and-water socialism" of Birmingham to the almost exclusively laissez-faire administrations of St. Petersburg and Madrid. In general private charities took charge of social services and private contractors built houses with privately-raised capital. Individual entrepreneurs, contractors and joint stock companies paid for utilities while property owners contributed to the improvement of paving, street widths and alignments, storm drains and sewers. Individual citizens paid property taxes, the main income of all cities and were always the best market for securities of their own municipalities. In return these private interests realized an increment in urban land values.